Peran Kepentingan Non Pengendali Dalam Pengaruh Fee Audit dan Ukuran Perusahaan Terhadap Audit Report Lag - Nidita Hafizna; Marhaendra Kusuma; Agus Athori (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - The objective of this study is to investigate and analyze the effects of audit fees, company size, and non-control factors on the quality of auditors' reports for manufacturing companies listed on the Bursa Efek Indonesia (BEI) from 2019 to 2023. Method - The data analysis technique used was moderation regression analysis with SPSS version 25. Main Findings - The study's findings show if audit fees have a detrimental effect on audit report delays. Afterwards, the lateness of the audit report was unaffected by the company's size. While non-pengendali is important for strengthening the association between firm size and audit report lag, non-pengendali is important for strengthening the relationship between audit fees and audit reports. Theory and Practical Implications - In order to build a relationship between the business and the stakeholders, this study examines the compliance and agency theories, which highlight the need of time and attention in writing. Novelty - The novelty lies in the use of non-controlling interest variables as moderation. Keywords: Audit report lag ̧ audit fee, company size, non-controlling interests.